Reading literary works in a second language: Transaction and interaction - Sánchez, Marta (Universidad de Costa Rica, 2015)
Esta discusión explora cómo lingüística y /o barreras culturales pueden afectar la respuesta estética a un texto literario en lectores competentes a un segundo idioma. A medida que el marco teórico que apoya esta discusión tanto en la teoría del esquema y la teoría transaccional de Rosenblatt se han utilizado. Se sugiere aquí que los lectores de segunda lengua ya poseen esquemas suficiente de la lengua extranjera y la cultura como en la operación con un texto estético. En esta transacción la comprensión de lectura se puede evidenciar.This discussion explores how linguistic and /or cultural barriers can affect the aesthetic response to a literary text in proficient second language readers. As the theoretical frame supporting this discussion both schema theory and Rosenblatt's transactional theory have been used. It is suggested here that second language readers already possess sufficient schemata of the foreign language and culture as to transact with a text aesthetically. In this transaction reading comprehension can be evidenced.